2019
DOI: 10.1186/s12950-019-0215-1
|View full text |Cite
|
Sign up to set email alerts
|

Serp-2, a virus-derived apoptosis and inflammasome inhibitor, attenuates liver ischemia-reperfusion injury in mice

Abstract: Background Ischemia-reperfusion injury (IRI) is an antigen-independent, innate immune response to arterial occlusion and ischemia with subsequent paradoxical exacerbation after reperfusion. IRI remains a critical problem after vessel occlusion and infarction or during harvest and surgery in transplants. After transplant, liver IRI (LIRI) contributes to increased acute and chronic rejection and graft loss. Tissue loss during LIRI has been attributed to local macrophage activation and invasion with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Continuous infusion of vMIP-II decreased infiltrating hematogenous cells at the site of injury in a spinal cord contusion injury in rats, with associated reductions in neuronal loss and gliosis [150]. However, this study did not include an assessment of locomotor function, thus it remains to be seen whether chemokine antagonism with vMIP-II improves functional recovery, as seen with the poxvirus chemokine modulator M-T7 [61]. Gene transfer of vMIP-II by direct injection of plasmid DNA improved cardiac allograft survival when hearts were placed in the subcutaneous position of the ear pinnae of CBA/J recipients [151].…”
Section: Vmip-iimentioning
confidence: 93%
See 1 more Smart Citation
“…Continuous infusion of vMIP-II decreased infiltrating hematogenous cells at the site of injury in a spinal cord contusion injury in rats, with associated reductions in neuronal loss and gliosis [150]. However, this study did not include an assessment of locomotor function, thus it remains to be seen whether chemokine antagonism with vMIP-II improves functional recovery, as seen with the poxvirus chemokine modulator M-T7 [61]. Gene transfer of vMIP-II by direct injection of plasmid DNA improved cardiac allograft survival when hearts were placed in the subcutaneous position of the ear pinnae of CBA/J recipients [151].…”
Section: Vmip-iimentioning
confidence: 93%
“…In mouse models of aortic allograft transplants, Serp-2 significantly reduced inflammation and intimal hyperplasia, again with no detected side effects [50,51]. In a model of partial 70% warm ischemia-reperfusion injury in the liver (LIRI), Serp-2 treatment given systemically also improved survival over 10 days, reduced necrotic damage of the liver and lowered acute markers of liver damage [61]. Surprisingly, caspase-1, caspase-3 and caspase-8 activation were not suppressed, suggesting an alternative mechanism of protection potentially by inhibition of circulating inflammatory proteases.…”
Section: Serp-2mentioning
confidence: 94%
“…Moreover, specific inhibitors of inflammasome need to be examined under conditions of different warm ischemia times and percentages. A recent study shows that treatment with Serp-2, a virus-derived inhibitor of apoptosis and inflammasome, regulates the levels of caspase-1, 8 and 10, improving the survival of mice submitted to 90 min of partial (70%) warm ischemia [128]. Interestingly, a study by Yang et al, using an experimental model of hepatic I/R based on 45 min of 70% warm ischemia, showed that Z-VD-fmk, a pan-caspase inhibitor (including caspase-1), had no effect on I/R injury or on the number of TUNEL-positive cells and staining pattern (nucleus and cytosol) [129].…”
Section: Relevance Of Inflammasome In Hepatic Ischemia-reperfusionmentioning
confidence: 99%
“…Interestingly, a study by Yang et al, using an experimental model of hepatic I/R based on 45 min of 70% warm ischemia, showed that Z-VD-fmk, a pan-caspase inhibitor (including caspase-1), had no effect on I/R injury or on the number of TUNEL-positive cells and staining pattern (nucleus and cytosol) [129]. The authors noted the minor role of apoptosis, thus contesting a relevant role for inflammasome or pyroptosis in hepatic I/R, at least in conditions of 90 min of partial (70%) warm ischemia [128] or 30 min of total warm I/R injury [126]. Data suggest that future research should be focused on detailing the type of cell death (necrosis, apoptosis and/or pyroptosis) and the signaling mechanisms of cell death, to identify specific targets for attenuating hepatic I/R injury.…”
Section: Relevance Of Inflammasome In Hepatic Ischemia-reperfusionmentioning
confidence: 99%
“…Myxoma virus (MYXV) is a leporipoxvirus with well-known strict species-specificity and host-tropism to the European rabbit ( Oryctolagus cuniculus ) [ 16 ]. We have demonstrated the safety and immunotherapeutic efficacy of several MYXV immune modulators in a wide array of preclinical models [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. M-T7 is an MYXV-derived immune modulator with broad chemokine-binding activity and proven therapeutic potential in inflammation-related diseases.…”
Section: Introductionmentioning
confidence: 99%